2016
DOI: 10.1016/j.jacc.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Coronary Revascularization for the Treatment of Multivessel Coronary Artery Disease

Abstract: BACKGROUND Hybrid coronary revascularization (HCR) combines minimally invasive surgical coronary artery bypass grafting of the left anterior descending artery with percutaneous coronary intervention (PCI) of non–left anterior descending vessels. HCR is increasingly used to treat multivessel coronary artery disease that includes stenoses in the proximal left anterior descending artery and at least 1 other vessel, but its effectiveness has not been rigorously evaluated. OBJECTIVES This National Institutes of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 16 publications
1
35
1
1
Order By: Relevance
“…32 Guidelines are inconclusive about the most appropriate timing of treatment in patients presenting with NSTE-ACS and MVCAD at present. 22,23 Concerning treatment strategy, in current guidelines CABG is recommended over PCI in patients with a baseline SYNTAX score >22, with left main or three-vessel coronary artery disease involving the proximal LAD.…”
Section: 2223mentioning
confidence: 99%
“…32 Guidelines are inconclusive about the most appropriate timing of treatment in patients presenting with NSTE-ACS and MVCAD at present. 22,23 Concerning treatment strategy, in current guidelines CABG is recommended over PCI in patients with a baseline SYNTAX score >22, with left main or three-vessel coronary artery disease involving the proximal LAD.…”
Section: 2223mentioning
confidence: 99%
“…Thus, the similar patency rates of DES and SVG and the superiority of the LIMA‐LAD graft forms the fundamental basis for a hybrid coronary revascularization (HCR). HCR combines a minimally invasive sternal sparing coronary artery bypass for LIMA–LAD graft and PCI to non‐LAD coronary arteries . In an era focused on minimally invasive interventions, HCR aims to reduce recovery duration, hospital complications, and surgical trauma, while maintaining durability outcomes similar to that of CABG .…”
Section: Introductionmentioning
confidence: 99%
“…Three main options for the performance of CABG without sternotomy are now available (Table 3): (1) minimally invasive CABG, in which all areas of the heart are bypassed via a small left anterolateral thoracotomy, usually without the use of the heart–lung machine123; (2) robotic total endoscopic coronary bypass grafting, in which robotic techniques are used not only for internal mammary artery harvest but also for the performance of all graft anastomoses124; and (3) HCR, which combines the performance of a single LIMA‐LAD graft via a small anterolateral thoracotomy, with PCI to the other myocardial territories of the heart that require revascularization 125…”
Section: Minimally Invasive Cabg Total Endoscopic Coronary Artery Bymentioning
confidence: 99%
“…So far, observational data have suggested that these procedures are safe and that patients recover significantly faster than with CABG in the early postoperative period 125, 126, 127. Furthermore, there may also be benefits related to periprocedural morbidity compared with CABG 125…”
Section: Minimally Invasive Cabg Total Endoscopic Coronary Artery Bymentioning
confidence: 99%